Ruptured Superficial Femoral Artery Anastomotic Pseudoaneurysm after 30 Years - D. Baldwin; H. Mashbari; K. L. Chow; M. Sarhan (Case Reports in Vascular Medicine)
Introduction. Anastomotic pseudoaneurysms are a complication of vascular reconstructive surgery with the majority in the femoral region. Although rare, ruptured femoral anastomotic pseudoaneurysms have high mortality and require emergency surgery. Case Presentation. A 60-year-old male with a history of a left leg crush injury was treated with a superficial femoral artery interposition vein graft 30 years ago. He presented nowadays with a three-day history of severe pain in his left thigh. CT angiography demonstrated a ruptured anastomotic pseudoaneurysm with contrast extravasation into an intramuscular hematoma. He had significant scarring from his previous surgeries which made the leg hostile for an open repair. Therefore, percutaneous access selectively cannulated the left iliofemoral vasculature. An angiogram showed a distal superficial femoral artery pseudoaneurysm. Subsequently, two 10mmx15cm Viabahn covered stents (Gore & Associates, Flagstaff, AZ) were placed bridging healthy superficial femoral artery. A completion angiogram demonstrated no extravasation into the pseudoaneurysm. The patient recovered and was discharged home two days postoperatively. Conclusion. Ruptured femoral anastomotic pseudoaneurysms are traditionally repaired with open pseudoaneurysm excision and arterial reconstruction, although endovascular repair has been reported. Furthermore, most femoral anastomotic pseudoaneurysms form less than 10 years after initial operation. We present a unique case of ruptured superficial femoral artery pseudoaneurysm, 30 years after the initial operation. Endovascular stents offer effective treatment for ruptured anastomotic pseudoaneurysms.